Surreptitious ethnography: Following the paths of Angolan refugees and returnees in the Angola-Zambia borderlands - Neto, Pedro Figueiredo (2017)
Between 2012 and 2014, the study of Angolan refugees and returnees led me to conduct fieldwork in the Meheba Refugee Camp (Zambia) and along both sides of the border between Angola and Zambia. In the eyes of the involved authorities, however, not only was the moment not appropriate, the issues under analysis were not welcome either. The bureaucratic and institutional obstacles I found during fieldwork eventually led me towards more pragmatic strategies, sometimes challenging the common principles of anthropological methodology and ethics. Without any institutional support, being ‘on the move’, following the paths of my interlocutors or simply guided by their contacts, became not only the way to venture into their lives and understand their social and cultural reality, but turned out to be a tactic to preclude multi-sided control. In this article I will examine fieldwork challenges but also the kind of information gathered while conducting a surreptitious ethnography.